KONSELING ISLAM MELALUI TEKNIK REFRAMING DAN TERAPI SHALAWAT UNTUK MENINGKATKAN SELF ESTEEM PADA PELAKU PENCURIAN DI LEMBAGA PEMASYARKATAN KELAS IIA BANYUWANGI - Ilfiatun Nuroini; Yohandi, Yohandi; Miftahussurur, Wildan; Sulaiman, Akhmad Husam (Program Studi Hukum Keluarga Islam, Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
This study aims to analyze the effectiveness of Islamic counseling through reframing techniques and prayer therapy in increasing self-esteem in perpetrators of theft crimes in Class IIA Banyuwangi Correctional Institution. The background of this study is based on the low self-esteem of inmates due to social stigma, guilt, and psychological conditions during sentencing. The Islamic counseling approach was chosen because it is able to combine spiritual and psychological principles to help clients re-understand the meaning of life, improve self-perception, and build positive hope. The research method uses a qualitative approach with a case study design, involving the process of assessment, intervention, and evaluation of several inmates who meet the research criteria. Reframing techniques are used to help clients reinterpret negative experiences more constructively, while prayer therapy is applied as a spiritual relaxation technique to foster inner peace and closeness to Allah. The results of the study showed a significant increase in the aspect of self-esteem after participating in a series of counseling sessions, characterized by a change in mindset, better emotional control, and the emergence of motivation to improve themselves. This study concludes that the application of Islamic counseling with reframing techniques and prayer therapy is effective in increasing the self-esteem of inmates, and can be an alternative to personality development services in correctional institutions.